Effects of a Brief Early Start Denver Model (ESDM)–Based Parent Intervention on Toddlers at Risk for Autism Spectrum Disorders: A Randomized Controlled Trial - Rogers, Sally J. (2012)
OBJECTIVE: This study was carried out to examine the efficacy of a 12-week, low intensity (one-hour-per-week of therapist contact), parent-delivered intervention for toddlers at risk for autism spectrum disorders (ASD) ages 14–24 months and their families. METHOD: A randomized controlled trial involving 98 children and families was carried out in three different sites investigating the efficacy of a parent delivery of the Early Start Denver Model (P-ESDM) (which fosters parental use of a child-centered responsive interaction style that embeds many teaching opportunities into play) compared to community treatment as usual. Assessments were completed at baseline and 12 weeks later, immediately after the end of parent coaching sessions. RESULTS: There was no effect of group assignment on parent-child interaction characteristics or on any child outcomes. Both groups of parents improved interaction skills and both groups of children demonstrated progress. Parents receiving P-ESDM demonstrated significantly stronger working alliances with their therapists than did the community group. Children in the community group received significantly more intervention hours than those in the P-ESDM group. For the group as a whole, both younger child age at the start of intervention, and a greater number of intervention hours, were positively related to degree of improvement in children’s behavior for most variables. CONCLUSIONS: Parent-implemented intervention studies for early ASD have thus far not demonstrated the large effects seen in intensive treatment studies. Evidence that both younger age and more intervention hours positively affect developmental rates has implications for clinical practice, service delivery, and public policy.